If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = 7x + 9 Reorder the terms: -6 + 2x = 7x + 9 Reorder the terms: -6 + 2x = 9 + 7x Solving -6 + 2x = 9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -6 + 2x + -7x = 9 + 7x + -7x Combine like terms: 2x + -7x = -5x -6 + -5x = 9 + 7x + -7x Combine like terms: 7x + -7x = 0 -6 + -5x = 9 + 0 -6 + -5x = 9 Add '6' to each side of the equation. -6 + 6 + -5x = 9 + 6 Combine like terms: -6 + 6 = 0 0 + -5x = 9 + 6 -5x = 9 + 6 Combine like terms: 9 + 6 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| 2x+y=62.40 | | 28+2a=+7 | | 25v=-5 | | 3g-11=6+12(g+4) | | 50+5x=200+2x | | 3x-(-2x)= | | 2m-1=6+11(m+1) | | y=4(+5)-8 | | y=4(5)-8 | | y=4(4)-8 | | 3=-1+8x | | 6y-5x=0 | | 6x^2+7=0 | | 18-4y=-2(6+2y) | | y=4(-1)-8 | | 2y^2-2y+37=y^2+16 | | 6t+5(1-3t)= | | 2x^2-5x+2=(x-3)(x-2)+3x | | 4x+1=2x-17 | | -3+4m=2-3m | | N-12=50n+94 | | 2y=3x-8 | | -5x-6x=0 | | U=7(4n+35)+8(n+1) | | a+5=-5a-13 | | x-2.1=2.4 | | 15-x=13 | | x-9=-7x-9 | | 12-3(w-7)=15 | | -4y+5y=-4x+2(x-2)+4x+2 | | C=1000+80x | | (5x^2-3x+7)+(2x^2+9x-11)= |